Vole damage to planted tree regeneration conditioned by some environmental factors - Suchomel, J.; Purchart, L.; Heroldová, M. (Marta); Homolka, M. (Miloslav); Kamler, J. (Jiří); Tkadlec, E. (Emil) (2012)
Recently, a great effort has been applied in the Czech Republic to replace forest monocultures of coniferous species by mixed coniferous-broadleaved stands in a ‘close to nature’ composition. These reforestation activities are complicated by impact of vole species (above all Microtus arvalis, M. agrestis and Myodes glareolus) through damage to tree bark. To quantify the damage by voles, we conducted research in 4 forest areas on 7200 trees from 3 to 15 years of age (beech being the dominant tree species). The main pre-requisite factors responsible for damage were the cover and the height of weedy species in the clearings and the proportion of grasses and grass litter on the plots.